Linear and conformational epitopes of vicilin-buried peptides as a model for improved nut allergy diagnostics - Swientoniewski, Lauren T.; Rambo, Ian M.; Nesbit, Jacqueline B.; Cheng, Hsiaopo; Gipson, Stephen A. Y.; Jones, Stacie M.; Doan, Dieu T.; Dreskin, Stephen C.; Mustafa, S. Shahzad; Smith, Scott A.; Kulis, Michael D.; Rivers, Adam R.; et al. (Frontiers in Allergy, 2025)
IntroductionIndividuals allergic to peanuts (PN) may show IgE cross-reactivity to tree nuts, especially walnuts (WN), which often complicates diagnosis. Vicilin-buried peptides (VBPs), short segments within the N-terminal vicilin leader sequence (LS), contribute to cross-reactivity due to their ubiquitous, highly conserved and stable α-hairpin structures. The binding patterns of cross-reactive IgE to linear and conformational epitopes of PN and WN LSs and constituent VBPs may serve as a model for understanding clinically symptomatic cross-reactivity.MethodsSerum samples (n = 30) from primarily oral food challenge-positive individuals with PN allergy (PNA, 33%), WN allergy (WNA, 47%), and PN and WN allergies (PWA, 20%) were collected. These sera and a monoclonal IgE antibody (6D12) were examined for IgE binding with microarrays of overlapping peptides from native Ara h 1 LS [AH1LS, Ara h 1.0101 (26–84)] and recombinant Jug r 2 LS [JR2LS, Jug r 2.0101 (1–173)] and via direct and competitive inhibition ELISA with intact LSs and constituent VBPs from PN (AH1.1) and WN (JR2.1, JR2.2, JR2.3). A mixed model analysis assessed the contribution of IgE binding patterns to VBPs in relation to PNA, WNA, or PWA status.ResultsAll three intact WN VBPs bound IgE at similar frequencies, with individual sera showing varying preferences for specific VBPs. AH1.1 was less recognized by WNA individuals but more frequently recognized by PNA and PWA subjects. WN VBPs were recognized by PNA sera samples at rates comparable to AH1.1. Our data indicates that each VBP can bind to one IgE molecule with high affinity. In a competitive inhibition ELISA, combining VBP competitors did not enhance inhibition compared to the dominant VBP, suggesting that both high- and low-affinity VBPs compete for the same monoclonal IgE in serum. This observation was mimicked by 6D12, a monoclonal IgE against JR2.1.DiscussionCross-reactivity among VBPs most likely arises from monoclonal IgE binding to α-hairpin structures and their overlapping linear amino acid sequences. The combination of linear and conformational IgE binding patterns enabled us to differentiate between the WNA, PNA, and PWA groups in this study and may assist us in using AH1LS and JR2LS to distinguish PN and WN allergies in the future.